ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN PENGGUNAAN JASA KAPAL RORO GILI IYANG RUTE BAWEAN-PACIRAN - KHODIJAH, SITI (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Public transport that is safe, comfortable and has a competitive price always been desired by consumers, especially in isolated areas such as islands Bawean. Pt. ASDP ferry is one of the companies providing Gili Iyang Ships transportation services, with the aim of provide crossing transport in isolated areas with the facilities offered to meet the needs of consumers. The companies are expected to understand behavior of consumers, so the company is able to determine the needs, wants and expectations of its consumers. This research was conducted to determine the factors that influence the consumer’s decision to use the sea transport of Roro Gili Iyang Ship Bawean-Paciran route or otherwise. This research is a quantitative research with the method of observation of interviews, questionnaires and documentation. Questionnaire was given to 75 respondents from Roro Gili Iyang ship Bawean-Paciran route users service, so that researchers get the data to test the validity, reliability and factor analysis. The data obtained the result that research shows factors affecting consumer in using services ship roro gili iyang route bawean- paciran was a necessity, learning process, lifestyle, culture, family, friends, income, work, information media, tariff tickets, service, physical evidence, security and comfort. For factors the most dominant factor is a job with total variant of 19, 425 %. Keywords: Factor Analysis, the using decision, Roro Gili Iyang Ship